Water-Based Cooling in PV Systems: A Statistical Comparison of Modified PV-T and Conventional PV Panels Under Variable Flow Rates - Saadi, Hasna; Korzenszky, Péter; Hermanucz, Péter (Journal of Central European Green Innovation, 2025)
This study explores how well a modified photovoltaic (PV) panel with a water-based cooling system performs under various environmental conditions. We compared a standard PV panel to one enhanced with copper pipes and aluminium adhesive, testing two different flow rates (4 l/min and 7 l/min) to see how solar irradiance and ambient temperature affect the working temperature. Our findings revealed that lower flow rates made the panel more sensitive to environmental changes, with solar irradiance and ambient temperature accounting for up to 92.5% and 80.2% of the temperature variation, respectively. The ANCOVA analysis confirmed that flow rate, solar irradiance, and ambient temperature all significantly influence the working temperature, with flow rate having the strongest impact. The results also showed a significant interaction between flow rate and irradiance, indicating that cooling effectiveness changes with sunlight intensity. However, the interaction between flow rate and ambient temperature was not significant, suggesting that the effect of flow rate remains consistent across different air temperatures.
Keywords: water-based cooling; flow rate; solar irradiance; ambient temperature; thermal performance; ANCOVA